Pengembangan Learning Log untuk Siswa SMP pada Pembelajaran Pemanasan Global dengan Metode Demonstrasi Berbasis POE - Widyastuti, Hilda Asri; Suhara, Suhara; Wulan, Ana Ratna (Department of Biology Education, Universitas Pendidikan Indonesia, 2018)
This study aims to describe the development of learning log for junior high school students on global warming with demonstration based on Predict-Observe-Explain (POE). The development process started with the preparation of learning log, test trial to obtain the data to be repaired, and obtained learning log tools better. The method used was the descriptive method. Two classes in one of junior high school in Bandung were selected by cluster random sampling. Data collected through the assignment of learning log, field notes through observation and interviews. The instruments were examined in this study is learning log’ task and rubric. While research instruments consisted of student’s and teacher’s interviews guides, field notes, and rubric for assessment authentic’s effectiveness. The trial showed that questions in task still need to be improved in terms of the sentence and the editorial content, rubrics for learning log developed based on the responses of the students. Meanwhile, the effectiveness of authentic assessment test phase is (45%) quite good. The results of the application authentic assessment can measure students' POE. Questions on the task and the rubric developed well. The effectiveness of authentic assessment in application phase is (85%) very good. The response of students and teacher about authentic assessment developed positively.